Mr. Lincoln's forts : a guide to the Civil War defenses of Washington - Cooling, Benjamin Franklin, III, 1938- (Scarecrow Press, 2010)
During the American Civil War, Washington, D.C. was the most heavily fortified city in North America. To protect Washington with all it contained and symbolized, the Army constructed a shield of fortifications: 68 enclosed earthen forts, 93 supplemental batteries, miles of military roads, and support structures for commissary, quartermaster, engineer, and civilian labor force, some of which still exist today. Revised in style, format, and content, the new edition of Mr. Lincoln's Forts is the premier historical reference and tour guide to the Civil War defenses of Washington, D.C.